In Praise of Slacking: Richard Linklater’s Slacker and Kevin Smith’s Clerks as Hallmarks of 1990s American Independent Cinema Counterculture - Małecka, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Some people live to work, others work to live, while still others prefer to live lives of leisure. Since the Puritans, American culture and literature have been dominated by individuals who have valued hard work. However, shortly after its founding, America managed to produce the leisurely Rip Van Winkle, who, over time, has been followed by kindred spirits such as, for instance, Walt Whitman, Henry David Thoreau, Twain’s Huck Finn, Melville’s Bartleby, Jack Kerouac, Diane di Prima, the Hippies, and Christopher McCandless. With the rise of the Indie Film movement of the 1990s, so came the rise of the slacker film. Films such as Slacker (1991), Singles (1992), Wayne’s World (1992), Reality Bites (1994), Clerks (1994), Kicking and Screaming (1995), Mallrats (1995), Chasing Amy (1997), The Big Lebowski (1998), and Office Space (1999) filled theatres over the decade with characters who take an unorthodox view of work and stress the importance of leisure in life. This essay discusses two slacker films, Richard Linklater’s Slacker (1991) and Kevin Smith’s Clerks (1994), which defined the slacker phenomenon in the 1990s and constituted two important landmarks in American independent film. While many of us may find the slacker pathetic and annoying, this essay argues that there is much value to be found in this healthy counterculture. By offering their perspectives on issues such as the Puritan work ethic, work-incited self-importance, leisure versus idleness and human relationships, Linklater and Smith join the preceding generations of slackers, providing a much needed balance to the American obsession with work and success.